A critical discourse analysis of the role of influencers in driving social change through Indonesian Youtube content - Yusanto, Freddy; Nugroho, Catur (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Communication mediated by social media presents content creators who have many followers who are then often called influencers. This study seeks to analyze the contributions of influencers who should act and be responsible as individuals who can convey public opinion through digital platforms. The researcher uses a qualitative research method with a critical discourse analysis approach to dismantle and reveal how influencers are strongly committed to spreading positive discourse as a form of responsibility as part of social change agents in the digital world. The object of the study is YouTube content from the accounts of Ria Ricis, Atta Halilintar, and Frost Diamond, which represent significant influencers in Indonesia. Researchers found that three significant influencers in Indonesia have not been able to carry out their duties as agents of social change. There are three reasons why influencers in this study are unable to carry out their duties and responsibilities as social change agents, namely the absence of a clear definition of the role of influencers as social change agents, the lack of understanding of influencers regarding their social responsibilities as social change agents, and the absence of an operational model that explains the concrete steps taken by influencers as effective social agents. This study provides recommendations on the duties and responsibilities of influencers as agents of social change in a model that the researcher calls the Content Development Model. This model consists of four main stages at the concept level (Input, Process, Output, and Outcome) and six execution stages at the technical level (Content Created, Interaction Distribution, Formation of Discourse, Change in Attitude and Behaviour, Collective Action and Social Change). This Content Development Model explains how influencers must produce content by considering positive social issues as agents of social change in society.